VD_FINDINFO HC / 2018 / 1072 vom 13. November 2018 - VD Tribunal cantonal (2018)
EXÉCUTION FORCÉE, SENTENCE ARBITRALE, AMENDE, POUVOIR DE REPRÉSENTATION | 341 al. 1 CPC (CH), 343 al. 1 let. c CPC (CH)